Studi Pengolahan Air Limbah Rs. Pelamonia Dan RSUP. Dr. Wahidin Sudirohusodo Makassar Tahun 2016 - Andi Rizki Syamsul Bahri; Abd Gafur (Celebes Enviromental Science Journal, 2019)
Each hospital has a way of waste water treatment and waste water treatment technologies are different. This study aims to determine the waste water treatment in Pelamonia Hospital and Dr. Wahidin Sudirohusodo hospital in Makassar on 2016. Type of research used in this study was observational descriptive approach. Samples in this research of the liquid waste was on Inlet and Outlet hospital. The results showed that in RS. Pelamonia obtained parameters were not qualified at a average BOD at the point of inlet 261.45 mg/L, COD at the inlet point of 355.7 mg/L and the outlet point 121.1 mg/L. Whereas in Dr. Wahidin Sudirohusodo hospital obtained parameters were not qualified at an average BOD at the point of inlet 263.94 mg/L, at the outlet point of 139.45 mg / L, COD at the inlet point of 563 mg/L, and the outlet point of 350.5 mg/L.The efficiency of waste water treatment of Pelamonia hospital including highly efficient category while the efficiency of waste water treatment of Dr. Wahidin Sudirohusodo hospital categorized fairly efficient. Preferably at a subsequent researchers examined other factors that affect the efficiency of waste water treatment.